(untitled) (Journal of Global Humanities and Social Sciences, 2024)
With the continuous development of globalization, the importance of translation, as an important means of cultural exchange, is becoming more and more prominent. Ecological Translation Studies provides a new perspective to understand and practice translation activities. As an important cultural heritage in northern China, the translation of public notices in Yulin Historical and Cultural Neighborhood is not only a task of language conversion, but also a process of cultural transmission and adaptation. The purpose of this paper is to explore how to effectively deal with the translation problems in this specific cultural environment under the framework of ecological translation studies, and to propose practical translation countermeasures.